Oro-Dental Pharmacovigilance in the Digital Age: Promoting Knowledge, Awareness, and Practice in Italy through a Smart Combined System-A Conference at the 30th National Congress of the Italian College of University Professors of Dental Disciplines - Gaetano La Mantia; Fortunato Buttacavoli; Vera Panzarella; Giuseppe Colella; Annalisa Capuano; Liberata Sportiello; Gaspare Parrinello; Ilaria Morreale; Giacomo Oteri; Giuseppe Bellavia; Vittorio Fusco; Rodolfo Mauceri; et al. (MDPI AG, 2023)
Adverse drug reactions (ADRs) represent a significant threat to patients' safety in dentistry, necessitating proactive measures for prevention and treatment. However, identifying ADRs of dental and oral interest can be challenging, and underreporting remains a persistent issue globally. This paper illustrates a smart system to help Italian healthcare personnel, including dentists, in identifying and reporting dental and oral ADRs. This educational program is within a larger multi-regional project financed by the Italian Agency of Drugs (AIFA). The proposed system comprises a free online questionnaire on ADRs of dental interest (including specific items about awareness and attitudes), and after the free consultation of an atlas of clinical images of dental and oral ADRs linked with a digital synopsis of drugs potentially related to ADRs. This section of the project was presented in April 2023 at the 30th National Congress of the Italian College of University Professors of Dental Disciplines, and the system appears to hold tremendous potential to improve the knowledge of healthcare professionals on oral and dental ADRs.